Language Style Used by Donald Trump on Instagram Captions Before and After Being Inaugurated as President of United States - Fitri, Nurul; Syukur, Helmi; Surya Darmadali, Waode (Journal of Islamic Culture and Literature (JICeL), 2024)
This study aims to analyze the style of language used by Donald Trump in writing captions on Instagram. This study focuses on the theory of Martin Joos (1976) which discusses the types of language style, and divides them into five, namely frozen, formal, casual, consultative, and intimate style. Then, this study was analyzed using a descriptive approach. In conducting this research, researcher focused on Donald Trump’s Instagram account by looking for the captions that could be used as data source based on the theory.  In this study, there are three types of language styles found, namely formal style, casual style, and intimate style.The style most commonly found is the formal style, while frozen and consultative styles are never found. The researcher concludes that the formal style is most widely used because it is related to work, and the situation that Donald Trump often faces. The frozen style and consultative style have never been found because these two styles are often used in speaking.Keywords: Language Style, Caption, Instagram